2017
DOI: 10.1111/and.12760
|View full text |Cite
|
Sign up to set email alerts
|

In vitro antioxidant effect of curcumin on human sperm quality in leucocytospermia

Abstract: Decreased sperm quality was caused by oxidative stress in semen from patients with leucocytospermia. Curcumin is a traditional Chinese herbal monomer extracted from Zingiberaceae turmeric and zedoary turmeric and has antioxidative and anti-inflammatory effects. This study aimed to investigate the effects and specific molecular mechanisms of curcumin on sperm quality in patients diagnosed with leucocytospermia. Forty cases of semen samples were collected from patients with leucocytospermia and 35 cases from nor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(22 citation statements)
references
References 17 publications
(17 reference statements)
1
15
0
1
Order By: Relevance
“…It affects the mobility of human spermatozoa and its function in vitro and in vivo fertility (Naz and Lough, 2014). Studies have demonstrated the potential of curcumin for the development of a novel intravaginal contraceptive (Zhang et al, 2017). Diarylheptanoids isolated from D. spongiosa such as diospongin B and C are found to exhibit anti-osteoporotic activity by inhibiting the release of 45 Ca on the resorption of bone tissues, the same was compared with standard drug elcitonin (Yin et al, 2004a).…”
Section: Other Bioactivities Of Diarylheptanoidmentioning
confidence: 99%
“…It affects the mobility of human spermatozoa and its function in vitro and in vivo fertility (Naz and Lough, 2014). Studies have demonstrated the potential of curcumin for the development of a novel intravaginal contraceptive (Zhang et al, 2017). Diarylheptanoids isolated from D. spongiosa such as diospongin B and C are found to exhibit anti-osteoporotic activity by inhibiting the release of 45 Ca on the resorption of bone tissues, the same was compared with standard drug elcitonin (Yin et al, 2004a).…”
Section: Other Bioactivities Of Diarylheptanoidmentioning
confidence: 99%
“…Polyphenols, such as resveratrol and curcumin, are well known agents able to modulate methyltransferase and histone deacetylase enzyme activities, thus being potential candidates for intentional modulation of epigenetic dynamics in spermatogenesis [ 248 ]. Indeed, such molecules are under investigation in the field, showing promising beneficial effects in ameliorating spermatogenesis in obese conditions both in animal models and in humans [ 275 , 276 , 277 , 278 ]. Concentration of factors as zinc in seminal fluid modulates protamine formation and dynamically chromatin structure, as a consequence [ 279 ].…”
Section: Epigenetic Mechanisms Are Sensitive To Environment and LImentioning
confidence: 99%
“…В исследованиях іn vitro было установлено антиоксидантное действие куркумина на качество спермы человека при лейкоцитоспермии. Проведение инкубации спермы с признаками лейкоспермии с куркумином с последующим компьютерным анализом спермы установило снижение в ней уровня гидроперекисей и повышение подвижности сперматозоидов [48].…”
Section: с е к с о л о г и я и а н д р о л о г и яunclassified